LEADERSHIP STYLES ON EMPLOYEE PERFORMANCE WITH WORK SATISFACTION AND ORGANIZATIONAL COMMITMENT AS INTERVENING VARIABLES - Alamanda, Sandya; Setiawan, Margono; Irawanto, Dodi Wirawan (Jurnal Aplikasi Manajemen, 2022)
This study aims to examine and analyze the influence of leadership style on employee performance with job satisfaction and organizational commitment as an intervening variable at PT. PLN (Persero) North Surabaya Area. This research was conducted using a questionnaire to 120 employees of PT. PLN (Persero) Area North Surabaya. Then the data is analyzed by using Partial Least Square (PLS). This study examines the direct and indirect effects. The result of this study states that leadership style can provide the effect of improving employee job satisfaction. Leadership style can affect increasing organizational commitment. Leadership style can give influence in improving employee performance. Job satisfaction cannot have an effect on improving employee performance. Organizational commitment can affect improving employee performance. Leadership style cannot give indirect influence in improving employee performance through job satisfaction. Leadership style can have an indirect influence on improving employee performance through organizational commitment.